Eosinophilia as a first sign of Hodgkin's lymphoma – A case report - Milošević, Rajko; Leković, Danijela; Antonijević, Nebojša; Bogdanović, Andrija (Vojnosanitetski pregled, 2017)
Introduction. It is well known that eosinophilia appears in a malignant disease. Frequency of all Hodgkin`s lymphoma patients is estimated to about 15%. Prognostic importance of this phenomenon is not completely investigated. Therefore we decided to present a female patient with eosinophilia, six months before lymphoma appearance. Case report. We presented a 51- years old female, from Serbia, who had eosinophilia (1,530–2,040 eosinophils per µL of blood), six months before Hodgkin's lymphoma appearance. Eosinophilic granuloma was confirmed by tumor’s biopsy and histopathologic examination, from the right femoral region. As eosinophilia was increasing, lymph nodes became enlarged (120 × 65 mm diameter), in the right parailiac region. All infectious and allergic examinations did not reveal eosinophilia's cause. Histopathologic revision was made with added immunohistochemical stains 17 months after tumor's biopsy. The diagnosis was changed from eosinophilic granuloma to mixed cellularity Hodgkin's lymphoma. After conducted Ann Arbor staging classification, II B clinical stage was established. The treatment was done by chemotherapy according to adriamycin, bleomycin, vinblastine, dacarbarine (ABVD) protocol, with 6 courses. Complete remission of the disease was achieved after 4 courses. Eosinophils number dropped to 640 per μl blood. Conclusion. Eosinophilia without revealed cause can precede Hodgkin's lymphoma. We suggest careful search for enlarged lymph nodes, anywhere in the patients’ body who suffer from eosinophilia. Timely and accurate histopathologic diagnostic is a right way to resolve such conditions.
Keywords: eosinophilia; hodgkin disease; signs and symptoms; diagnosis; abvd protocol; treatment outcome